2022 IJSPT Orthopedic Summit Research Abstracts - International Journal of Sports Physical Therapy (North American Sports Medicine Institute, 2022)
The International Journal of Sports Physical Therapy is pleased to publish abstracts from the 12th Orthopaedic Summit (OSET) taking place in Boston, September 21-24, 2022. The IJSPT hosted the 2nd annual research forum and reception at OSET, sponsored by ATI Physical Therapy and Hyperice. The abstracts presented in the following pages were selected by the OSET Research Committee and editorial staff of the International Journal of Sports Physical Therapy. After careful review, a total of 17 research abstracts were accepted and presented at OSET 2022. Awards for outstanding abstracts were presented on September 23rd. The 2022 abstracts include contemporary orthopaedic and rehabilitation topics across various research designs. Each abstract presents only a brief summary of a research project / presentation and does not permit full assessment of the scientific rigor with which the work was conducted. While the abstracts offer only preliminary results that may require further refinement and future validation, they do serve an important role in sharing new research ideas and rehabilitation advancements. This sharing of ideas helps to encourage dialogue among researchers, clinicians, and educators that will ultimately contribute to the orthopaedic and rehabilitation body of knowledge. We strongly encourage authors to continue pursuing the publication of their research as a full manuscript. Thank you to all submitting abstracts for consideration. We look forward to another outstanding season of submissions for OSET 2023. _Phil Page PhD, PT, ATC_ _Chuck Thigpen PhD, PT, ATC_ OSET Research Committee Co-Chairs